Strategies And Structures For Diversification - Pitts, Robert A. (Academy of Management Journal, 1977)
This paper describes a study of corporate technological staff size in 21 large, diversified firms. The marked bimodality of the resulting data suggests that sample firms are avoiding intermediate positions between vigorous pursuit of interdivisional sharing of technological resources and deliberate avoidance of such sharing. Implications for diversification are explored.